2021
DOI: 10.3390/s21082876
|View full text |Cite
|
Sign up to set email alerts
|

Development of Piezoelectric Energy Harvester System through Optimizing Multiple Structural Parameters

Abstract: Road power generation technology is of significance for constructing smart roads. With a high electromechanical conversion rate and high bearing capacity, the stack piezoelectric transducer is one of the most used structures in road energy harvesting to convert mechanical energy into electrical energy. To further improve the energy generation efficiency of this type of piezoelectric energy harvester (PEH), this study theoretically and experimentally investigated the influences of connection mode, number of sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…With the approach developed in this paper, we can measure the fuzzy cross-efficiency scores for cases of variable returns to scale with fuzzy observation and apply to different fields of engineering applications (e.g., [42][43][44][45][46][47]) for decision-making. In this paper, the inputs and outputs are treated as triangular fuzzy numbers.…”
Section: Discussionmentioning
confidence: 99%
“…With the approach developed in this paper, we can measure the fuzzy cross-efficiency scores for cases of variable returns to scale with fuzzy observation and apply to different fields of engineering applications (e.g., [42][43][44][45][46][47]) for decision-making. In this paper, the inputs and outputs are treated as triangular fuzzy numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Waveforms such as sinusoidal form, half-wave sinusoidal form, and haversine form can be chosen [35,36]. In this case, the vehicle load was simplified as a sinusoidal wave [22], which can be calculated by Equation ( 14):…”
Section: Effect Of Load Impedancementioning
confidence: 99%
“…Existing studies have shown that piezoelectric units installed in pavement suffer structural damages, such as interfacial shear failure, corner breaks, and electrode detachment [20,21]. Recent research has been shifted to assemble the piezoelectric transducers into arrays and fabricated them into a protective package to improve the energy conversion efficiency, structural strength, and service performance [22,23]. Roshani conducted uniaxial compression tests on piezoelectric devices and found that the number and arrangement of piezoelectric units influenced the output power [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [33], the authors designed an energy harvester to extract energy from a smart road. The authors investigated the number of stacks layers, influences of connection mode, number of units and ratio of height to cross-sectional area [33].…”
Section: Introductionmentioning
confidence: 99%